2017
DOI: 10.1016/j.ccm.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Pneumonia

Abstract: SUMMARY CAP due to Legionella, Chlamydophyla, or Mycoplasma continues to be a diagnostic challenge due to the nonspecific clinical and radiographic presentations. The vague clinical presentations of atypical CAP contribute to its underdiagnosis and under-reporting. Advancements in diagnostic techniques bring hope to rapid and accurate diagnosis of atypical CAP. Macrolides and respiratory fluoroquinolones are currently the antibiotics of choice, but this may change in the near future as more antibiotics resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 100 publications
0
45
0
7
Order By: Relevance
“…The increasing empirical use of macrolides for pneumonia has been observed in high-income countries, such as the USA, due to their broader spectrum activity against atypical pneumonia caused by Mycoplasma pneumoniae, Chlamydia pneumoniae, and Bordetella pertussis. [53][54][55] The increase in penicillin and erythromycin resistance could be due to acquisition of resistance determinants (eg, mefA in GPSC3 in the USA), the expansion of extant nonvaccine serotypes within a well established resistant lineage (eg, penicillin-resistant lineage GPSC5 replacing its major serotype composition from serotype 23F to 35B/D in South Africa), or simply a clonal expansion of a non-vaccine-type lineage with antimicrobial resistance (eg, penicillin and macrolide resistant GPSC59 in the USA). Additionally, this study revealed differences in resistance prevalence within a single lineage between countries, indicating that some surviving lineages could acquire antibiotic resistance determinants adaptive to the local antibiotic selective pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing empirical use of macrolides for pneumonia has been observed in high-income countries, such as the USA, due to their broader spectrum activity against atypical pneumonia caused by Mycoplasma pneumoniae, Chlamydia pneumoniae, and Bordetella pertussis. [53][54][55] The increase in penicillin and erythromycin resistance could be due to acquisition of resistance determinants (eg, mefA in GPSC3 in the USA), the expansion of extant nonvaccine serotypes within a well established resistant lineage (eg, penicillin-resistant lineage GPSC5 replacing its major serotype composition from serotype 23F to 35B/D in South Africa), or simply a clonal expansion of a non-vaccine-type lineage with antimicrobial resistance (eg, penicillin and macrolide resistant GPSC59 in the USA). Additionally, this study revealed differences in resistance prevalence within a single lineage between countries, indicating that some surviving lineages could acquire antibiotic resistance determinants adaptive to the local antibiotic selective pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Current clinical guidelines have categorized pneumonia into four types: community acquired (CAP), healthcare associated, hospital acquired [1] and ventilator associated [ 2 ]. Among these, CAP is identified as infection in a patient with no recent contact with the healthcare system [ 3 ]. Mycoplasma pneumoniae , Chlamydia pneumoniae and Legionella pneumophila are the most common bacterial agents of atypical CAP [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…L. pneumophila mainly affects elderly people and more often men than women. This bacterium is rarely differentiated from other atypical pneumonia because it presents similar clinical signs and symptoms [ 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The white blood cell counts of viral infection is normal in most cases, as well as M. pneumoniae infection. It is difficult to distinguish M. pneumoniae from virus-induced LRTI (Sharma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%